Umbilical Cord Blood Natural Killer Cells, Their Characteristics, and Potential Clinical Applications - Sarvaria, Anushruti; Jawdat, Dunia; Madrigal, J. Alejandro; Saudemont, Aurore (Frontiers in Immunology, 2017)
Natural killer (NK) cells are lymphocytes of the innate immunity able to kill different targets such as cancer cells and virally infected cells without prior activation making then attractive candidates for cancer immunotherapy. Umbilical cord blood (UCB) has become a source of hematopoietic stem cells for transplantation but as we gain a better understanding of the characteristics of each immune cells that UCB contains we will also be able to develop new cell therapies for cancer. In this review, we present what is currently known of the phenotype and functions of UCB NK cells and how these cells could be used in the future for cancer immunotherapy.